2022
DOI: 10.1523/jneurosci.2203-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Evidence Accumulation Using Optic Flow in a Naturalistic Navigation Task

Abstract: Sensory evidence accumulation is considered a hallmark of decision-making in noisy environments. Integration of sensory inputs has been traditionally studied using passive stimuli, segregating perception from action. Lessons learned from this approach, however, may not generalize to ethological behaviors like navigation, where there is an active interplay between perception and action. We designed a sensory-based sequential decision task in virtual reality in which humans and monkeys navigated to a memorized l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…Together, these findings shed light on how to bridge the gap between AI and neuroscience [3, 4, 18, 19]: from AI to neuroscience, our work validates the rationale of the brain’s inductive biases in spatial navigation [20, 17]. From neuroscience to AI, our work exemplifies how insights from the brain can inspire the development of AI with better generalization abilities.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Together, these findings shed light on how to bridge the gap between AI and neuroscience [3, 4, 18, 19]: from AI to neuroscience, our work validates the rationale of the brain’s inductive biases in spatial navigation [20, 17]. From neuroscience to AI, our work exemplifies how insights from the brain can inspire the development of AI with better generalization abilities.…”
Section: Introductionsupporting
confidence: 69%
“…Training agents with greater uncertainty in observation than prediction biases agents toward ignoring observations in belief formation, which then cripples their generalization abilities in novel tasks that require the use of novel observations to construct the belief, instead of the outdated internal model. Therefore, to generalize, agents must develop prior knowledge of relying more on observation, similar to macaques and humans in this task [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is one among the few recent studies that tested self-motion perception under a direct coupling between the actions of the participants and the sensory feedback (25)(26)(27). These recent experiments imposed fewer artificial constraints than the traditional open-loop psychophysical paradigms on self-motion perception (e.g., [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Under the assumption that the firing rates of neurons in the VN reflect sensory predictions errors (16, 45), this suggests that no steering-related predictions about the vestibular reafference are made in the VN. Even though the vestibular cerebellum is often suggested to house the internal model for self-motion estimation because of its projections to the vestibular nuclei (46), the internal model of the mapping between steering movements and self-motion seems located on a more downstream level within the vestibular processing pathway (25). This is in line with observations during the processing of the visual reafference of steering movements; Page and Duffy (22) reported that neurons in the medial superior temporal area in monkeys responded differently to optic flow cues resulting from steering movements compared to passive viewing of the same optic flow cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation